Studies in Health Technology and Informatics Volume 20 - Telematics in Primary Care in Europe - Maeseneer, J. De (IOS Press, 2014)
In June 1992, national representatives of the 12 EU-memberstates and leaders of different AIM-projects, related to primary care, met in Brussels. The AIM-office convened this meeting because of their concern that primary health care was not well represented within the AIM-projects. There was a view that, while several AIM-projects were developing highly sophisticated telecommunications systems, the average general practitioner in Europe continued to use paper and pen and was still communicating by post and telephone. The ambitious task of the Concerted Action was to bridge the gap between the developments in telematics and the daily practice of European General Practitioners. An enthusiastic Project Management Group was elected by the meeting and started to work in October 1992. The group was composed of people with very different backgrounds.